Research on the Innovation Path of University Ideological and Political Work Based on Big Data Technology. Issue 2 (October 2020) - Tang, Lanlan
Abstract: Ideological and political work is one of the concrete forms of higher education. The effectiveness of education determines the teaching quality of Ideological and political work for college students. In the context of the era of big data, the "5V" characteristics of big data not only bring convenience to the development of the era, but also bring new opportunities to ideological and political work. Ideological and political work in Colleges and universities should combine the characteristics of big data. Through the establishment of scientific big data thinking, colleges and universities can explore and publish innovative ideological and political work paths.